Ingestible Sensor Based on Fluorescent Gold Nanoparticles and Molecularly Imprinted Polymers on Thread for Localized Quantification of Escherichia Coli in the Gastrointestinal Tract - Khachornsakkul, Kawin; Del-Rio-Ruiz, Ruben; Zeng, Wenxin; Martins dos Santos, Danilo; da Silva, Debora Regina Romualdo [UNESP]; Widmer, Giovanni; Sonkusale, Sameer (Wiley, 2024)
The small intestinal (SI) microbiota plays an important role in human health and disease. Current methods based on fecal analysis do not provide an accurate representation of the SI microbiome. This article introduces an ingestible sensor for the quantification of Escherichia coli (E. coli) in the SI by developing the fluorescent thread-based ingestible pill analytical device (TPAD) using fluorescent gold nanoclusters (AuNCs) coupled with molecularly imprinted polymers (MIPs). Quantitative detection lies in the change in fluorescence signal on thread as proportional to target bacteria concentrations using a smartphone. Utilizing a pH-sensitive enteric coating, this device facilitates localized sampling of the SI microbiome. Hydrophilic beads are employed to autonomously seal the device after sampling, offering a self-locking mechanism. The sensor demonstrates a linear range for E. coli detection between 2.0 × 103 and 14.0 × 103 CFU mL−1 with an R2 of 0.9975 and a detection limit (LOD) of 400.0 × 102 CFU mL−1. The sensor also shows remarkable precision and acceptable accuracy for monitoring E. coli levels in in vivo animal studies compared to commercially available test kits. The developed TPAD, therefore, offers a novel, low-cost, and non-invasive method for rapidly diagnosing gastrointestinal (GI)-related medical conditions and studying host–microbiome interactions.
Keywords: Escherichia coli (E. coli); gastrointestinal (GI) tract; ingestible sensors; molecularly imprinted polymers (MIPs); nanomaterials; thread-based analytical devices (TADs)